An industrial quality control study on Union Refinery Corporation - Gonzales, Edello; Limpiada, Diane Mariel Madel; Pacete, Faye Ann. (Diliman, Quezon City College of Engineering, 2004)
Union Refinery Corporation is a subsidiary of UniOil Group of Companies that specializes on Industrial Lubricants and specialty fuel oils. For the past 47 years, they have established a growing share in the market for its quality products, making them one of the biggest local suppliers of lubricants. This study provides the application of Statistical Process Control and other quality tools and techniques to enable the company to further improve their quality both in products and in the processes. The group started by documenting the products and the process to gain sufficient information to be used for the analysis of the problems encountered by the company. Two major problems were selected by the group to focus on this project: 1) Blend being out of Specifications 2) Over/Under Filling of Lubricant Containers. Analysis of these problems was conducted using Statistical Process Control (SPC) tools and Ishikawa Diagrams. Results of the analysis on the problem of blend being out of specifications show high variability in the kinematic viscosity @ 100 deg.C of Uniplus 2T. The group suggests the following recommendations; 1. Evaluation of operator performance 2. Inspection of the materials on the supplier's facility 3. Scheduling regular preventive maintenance 4. Training on the effective use of statistical process control tools. On the other hand, analysis on the filling process of the company suggests that underfilling and overfilling could be avoided if the following recommendations would be implemented: 1. Introduction and Implementation of Statistical Process Control 2. Implementation of a Standard Approach for Acceptance Sampling 3. Improvement of the readability of the Machine Readings 4. Implementation of a Stricter Rule on Vendor-Sourcing.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Union Refinery Corporation; Oil industry; Quality Control